EU bank resolution and investing in contingent convertible instruments: an exploratory study of the Banco Popular bail-in - Reffet, Théophile Pierre Jean (2020)
In the wake of the 2008 financial crisis, an extensive toolbox was deployed through Basel III accords to address the eventuality of a bank failure, including the Single Resolution Mechanism, which was put to the test through Banco Popular’s resolution in June 2017. Holders of equity, AT1, AT2 were wiped out far below breaching trigger levels while contagion to the rest of the market was minimal, highlighting the idiosyncratic nature of the event. This research aims to understand the broader significance of this specific resolution event on the subordinate debt market and regulatory bodies, an angle that has been relatively unexplored in the literature. In order to collect information regarding investment rationales and market viewpoints, which is generally the property of insiders, interviews with seasoned professionals from the subordinate debt investment industry were conducted. As a result, the study shows that the Banco Popular resolution showcased the effectiveness of the SRM, despite a sales process which was led to fit the requirements of the only available buyer. The broader lessons of the event regarding CoCo structuring, capital structure valuation, and trigger levels are at odds with the recent shift in stance from the ECB following the Covid-19 crisis’ consequences.